Research Progress of Bile Acids in Cancer - Fu, Junhao; Yu, Min; Xu, Wenxia; Yu, Shian (Frontiers in Oncology, 2022)
Bile acids (BAs) were originally known as detergents to facilitate the digestion and absorption of lipids. And our current knowledge of BAs has been extended to potential carcinogenic or cancer suppressor factors due to constant research. In fact, BAs were regarded as a tumor promoters as early as the 1940s. Differential bile acid signals emitted by various bile acid profiles can produce distinct pathophysiological traits, thereby participating in the occurrence and development of tumors. Nevertheless, in recent years, more and more studies have noticed the value of BAs as therapeutic targets. And several studies have applied BAs as a therapeutic agent for various diseases including cancer. Based on the above evidence, we acknowledge that the role of BAs in cancer has yet to be exploited, although considerable efforts have been made to probe the functions of BAs. In this review, we describe the characteristics of BAs as a double-edged sword in cancer, hoping to provide references for future cancer treatments.